Key factors for developing sustainable wine tourism in the West Herzegovina Canton - Karamehmedović, Deša; Raspudić, Ante (Oeconomica Jadertina, 2024)
This study aims to provide a situational analysis of the current development of wine tourism in the West Herzegovina Canton, especially highlighting key factors for developing sustainable wine tourism as perceived by winery owners and/or managers. Scientific and professional literature, online sources, and empirical research using the e-Delphi technique were utilised to investigate the topic. In addition to quantitative data analysis, the results were analysed and explained using the PEST matrix. Low interest among public policy stakeholders in its development was identified as the most problematic issue, while the quality of wine was recognised as the most important opportunity. Taking into account all the issues and opportunities, and considering the broader context of the West Herzegovina Canton's development, key factors for developing sustainable wine tourism include: increasing the interest of public policy stakeholders and investments in wine tourism development; implementing comprehensive marketing strategies for the promotion of wine tourism and its placement in the tourist market; encouraging cooperation among all stakeholders, improving communication, and fostering synergy; educating winemakers and other stakeholders directly involved in wine tourism; enhancing ecological wine production and wine quality; expanding capacity and modernising existing wineries; promoting wine tourism and improving the region's image; developing other specialised forms of tourism; advocating for supportive public policies and removing administrative obstacles; and managing the sustainable development of wine tourism. The research limitations included the absence of the Vineyard and Wine Register, the lack of operational tourist boards in three out of four municipalities in the West Herzegovina Canton, and issues with participant engagement during the empirical research. Future research recommendations include verifying the factors listed in the study's limitations and examining the structure of wine tourism at the time, identifying weaknesses, strengths, opportunities, and threats. New empirical studies could uncover additional factors crucial for wine tourism development in the West Herzegovina Canton and Bosnia and Herzegovina.
Keywords: Development of wine tourism, sustainable development, West Herzegovina Canton.